Type 3 Thyroplasty for a Patient with Female-to-Male Gender Identity Disorder. (10th April 2018) - Saito, Yu; Nakamura, Kazuhiro; Itani, Shigeto; Tsukahara, Kiyoaki
Abstract : Objective . In most cases, about the voice of the patient with female-to-male/gender identity disorder (FTM/GID), hormone therapy makes the voice low-pitched. In success cases, there is no need for phonosurgery. However, hormone therapy is not effective in some cases. We perform type 3 thyroplasty in these cases. Method . Hormone therapy was started in 2008 but did not lower the speaking fundamental frequencies (SFFs). We therefore performed TP3 under local anesthesia. Results . In our case, the SFF at the first visit was 146 Hz. The postoperative SFF was 110 Hz. Conclusions . TP3 was performed under local anesthesia in a patient with FTM/GID in whom hormone therapy proved ineffective. With successful conversion to a lower-pitched voice, the patient could begin to live daily life as a male. QOL improved significantly with TP3. If hormone therapy proves ineffective, TP3 may be selected as an optional treatment and appears to show few surgical complications and was, in this case, a very effective treatment.